INFLUENCE OF BOLTED SPLICE CONNECTIONS ON THE GLOBAL BEHAVIOUR OF STEEL LATTICE TELECOMMUNICATION TOWERS (Collection of scientific works «Modern structures of metal and wood», 2023)
The bolted joints  in  the  leg  and  the bracing  members  of  the  lattice  transmission towers are always subjected to predominant axial forces, which will cause joint slip that greatly af-fects  the  global  behaviour  of  the  whole  structure.  The  paper  shows  the  results  of  the  numerical modelling of the response of the steel lattice communication tower, with height h = 40.5 m located in Rzeszów. A comparison was made of five tower models, differing in the characteristics of the joint  force-elongation  relationship,  including  stiffness  of  the  components  and  also joint  slippage, coming from Category A joints. The paper presents the difference in displacements and rotations of chosen tower panels, internal forces in leg members, as well as in the fundamental flexural frequen-cy obtained without considering the force-displacement characteristic and with four different ways of modelling of joints behaviour.